Alterations of the amplitude of low-frequency fluctuations in anxiety in Parkinson's disease. (6th March 2018) - Wang, Xixi; Li, Junyi; Wang, Min; Yuan, Yongsheng; Zhu, Lin; Shen, Yuting; Zhang, Hui; Zhang, Kezhong
Highlights: The increased activities of cerebellar posterior lobe, brainstem, orbitofrontal gyrus in anxiety in PD. The results were observed utilizing resting-state functional magnetic resonance imaging. Pivotal confounding factors such as severity depression were excluded in this study. Abstract: Object: Anxiety disorders are very common in Parkinson's disease (PD), but neural mechanisms underlying these symptoms still remain elusive. In the present study, we aim to investigate the neural substrates in anxiety disorders in PD. Methods: The present study comprised 48 PD patients and 19 healthy subjects. According to a Hamilton Anxiety Rating Scale cutoff score of 12, we divided PD patients into PD with anxiety groups (n = 15) and PD without anxiety groups (n = 33). Patients with apparent depressive symptoms and cognitive decline were excluded. All subjects were evaluated for demographic and clinical characteristics and performed 3.0 T MRI scans. The alterations of neural activity were examined utilizing resting-state fMRI (rs-fMRI) combined with the amplitude of low-frequency fluctuations (ALFF) approach. Results: Results of the analysis of covariance indicated that PD patients with anxiety displayed increased ALFF mainly in right cerebellar posterior lobe (CPL), bilateral brainstem and right orbitofrontal gyrus (OFG). Subsequently, the Spearman correlation demonstrated negative correlation between ALFF values in right cerebellum_9 and the Hamilton Anxiety Rating Scale scores. Conclusion: Our findings demonstrated that anxiety disorders in PD were associated with increased activities in anxiety-related brain regions, including OFG, brainstem and CPL, using the ALFF approach.